Politik Hukum Penegakan Tindak Pidana Pemilu Perspektif Keadilan Bermartabat - Munte, Herdi (Universitas Jember, 2023)
Election criminal law is built and enforced as a legal instrument for eradicating election criminal acts. In fact there is a demand to reform the legal politics of election crime enforcement from the perspective of dignified justice to create honest, fair and dignified elections. The problem studied is how the current law enforcement of election crimes is political and why it is important to reform the law enforcement politics of election crimes based on dignified justice. The research was conducted using a juridical-normative method with statutory and doctrinal approaches. The results of the study show that the regulation of election crimes is contained in a book of election law laws (UU No.7 of 2017 last amended by Law No.7 of 2023) there are as many as 67 articles consisting of offenses and crimes. Many criminal provisions are irrelevant, the enforcement of election criminal law is still far from what was expected, so it is necessary to reform law enforcement in a structured and systematic manner both from the aspect of substance, structure and legal culture. The politics of election criminal law currently places punishment as the foremost legal means, while the demands for the development of law enforcement for election criminal acts that are expected are punishment as a last resort and reform of law enforcement for election criminal acts based on dignified justice (justice that humanizes humans) a necessity in the context of guaranteeing legal objectives (fairness, benefit and certainty) and the objectives of holding elections that are fair and with integrity, legal certainty, effectiveness based on values, principles, norms and rules rooted in the spirit of the nation (volksgeid), namely Pancasila.Keywords: Legal Politics, Crime, Dignified Elections.